DEVELOPMENT OF AN OFF-AXIS DIGITAL HOLOGRAPHIC MICROSCOPE FOR THREE-DIMENSIONAL (3D) MICROFLUIDICS APPLICATION - HAWA, RINGKAI (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Mixing process in microfluidic devices has been widely employed in bio-, nano-, and environmental technologies for biomedical and health related issue i.e., early detection of malaria and diagnosis, and monitor the level of blood sugar in a body. It also extensively applied in chemical industries to detect heavy metal ions in groundwater. Digital holographic microscopy (DHM) is a promising three-dimensional fluid flow measurement technique as it can easily measure detailed microscale observation and visualization of flow field in real time. DHM uses digitally recorded hologram and computer algorithm to calculate the image of the object wave front. However, commercially available digital holographic microscope is not affordable to most research institutions and it is strictly limited to fluid moving in horizontal direction only. Therefore, it is imperative to develop a custom-made digital holographic microscope with an extra capability to observe and visualize fluid under the influence of gravitational force. The optical system was initially designed using a CAD software. Optical component and holders were fabricated using a 3D printer while the housing for the entire optical system was machined using a multi-axis milling machine. Linear step neutral density (ND) filter was used for calibration purpose. Once calibration of the optical system using Fourier Transform method was done, a custom-made microchannel was laser-cut to ensure precise dimensional accuracy. Thereafter, three-dimensional experimental flow mixing of 10-μm polystyrene microsphere suspended in water with Magnaflux Carrier II petroleum distillate carrier oil was conducted inside the fabricated microchannel. To get better and clearer images, the working distance of 10× microscope objective was increased from 16.5 mm to 18 mm. With resolution of 1280 pixels × 1024 pixels ThorCam camera, 10 μm microspheres in water can be seen clearly inside the 634 μm interior wall of the fabricated microchannel. The calculated total field of view of the camera is 853 μm × 683 μm. The experiment was successfully demonstrated using the developed digital holographic microscope. In order to improve the overall performance of the system, higher power objective lens and higher power laser are suggested to be used in the future.